Alteration of Regiospecificity in Biphenyl Dioxygenase by Active-Site Engineering - Suenaga, Hikaru (American Society for Microbiology, 2002)
Biphenyl dioxygenase (Bph Dox) is responsible for the initial dioxygenation step during the metabolism of biphenyl. The large subunit (BphA1) of Bph Dox plays a crucial role in the determination of the substrate specificity of biphenyl-related compounds, including polychlorinated biphenyls (PCBs). Based on crystallographic analyses of naphthalene dioxygenase (B. Kauppi, K. Lee, E. Carredano, R. E. Parales, D. T. Gibson, H. Eklund, and S. Ramaswamy, Structure 6:571-586, 1998), we developed a three-dimensional model of KF707 BphA1 of Pseudomonas pseudoalcaligenes KF707. Based on structural information about the amino acids which coordinate the catalytic nonheme iron center, we constructed 12 site-directed BphA1 mutants with changes at positions 227, 332, 335, 376, 377, and 383 and expressed these enzymes in Escherichia coli. The Ile335Phe, Thr376Asn, and Phe377Leu Bph Dox mutants exhibited altered regiospecificities for various PCBs compared with wild-type Bph Dox. In particular, the Ile335Phe mutant acquired the ability to degrade 2,5,2′,5′-tetrachlorobiphenyl by 3,4-dioxygenation and showed bifunctional 2,3-dioxygenase and 3,4-dioxygenase activities for 2,5,2′-trichlorobiphenyl and 2,5,4′-trichlorobiphenyl. Furthermore, two mutants, the Phe227Val and Phe377Ala mutants, introduced molecular oxygen at the 2,3 position, forming 3-chloro-2′,3′-dihydroxy biphenyl with concomitant dechlorination.